2015
DOI: 10.1021/acs.joc.5b01351
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II)-Mediated C(sp2)–H Hydroxylation

Abstract: A Cu(II)-mediated ortho-C-H hydroxylation using a removable directing group has been developed. The reaction exhibits considerable functional group tolerance. The use of O2 as an oxidant is crucial for the reactivity. Water is also found to significantly improve this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 70 publications
4
54
2
1
Order By: Relevance
“…In 2006, Yu and co‐workers reported the first example of copper(II)‐catalyzed ortho ‐hydroxylation of phenyl pyridines using molecular oxygen as the oxidant . Yu, Dai, Lin and co‐workers developed a method for the ortho ‐hydroxylation of benzamide derivatives in which the C−H functionalization is directed by a bidentate oxazolyamide group . Koley and co‐workers discovered a copper(I)‐catalyzed acyloxylation of indoline with benzoic acid coupling partners using O 2 as an oxidant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2006, Yu and co‐workers reported the first example of copper(II)‐catalyzed ortho ‐hydroxylation of phenyl pyridines using molecular oxygen as the oxidant . Yu, Dai, Lin and co‐workers developed a method for the ortho ‐hydroxylation of benzamide derivatives in which the C−H functionalization is directed by a bidentate oxazolyamide group . Koley and co‐workers discovered a copper(I)‐catalyzed acyloxylation of indoline with benzoic acid coupling partners using O 2 as an oxidant.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Yu, Dai, Lin and co-workers developed a method for the orthohydroxylation of benzamide derivatives in which the C À H functionalization is directed by a bidentate oxazolyamide group. [10] Koley and co-workers [11] discovered a copper(I)catalyzed acyloxylation of indoline with benzoic acid coupling partners using O 2 as an oxidant. Although aliphatic carboxylic acids were also tested as coupling partners, the yields were generally low (35 ∼ 55%).…”
Section: Cu-mediated C7 Acetoxylation Of Indolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, another ortho ‐C–H activation reaction of aromatic amides with amide‐oxazoline as the directing group and Cu(OAc) 2 as the catalyst was designed by Yu's team (Scheme ) . Interestingly, unlike the former reaction, the highlight of this reaction is that O 2 is the sole oxidant rather than air for the ortho ‐hydroxylation of aromatic amides.…”
Section: Ortho‐c–h Functionalization Of Aromatic Amidesmentioning
confidence: 99%
“…Thed etailed mechanistic investigations suggested that the reactionm ight go through aC u(OAc) 2 -mediated acetoxylation followed by ar apid hydrolysis.M orer ecently, Yu and co-workers also describedaC u(II)-mediated ortho-C À Hh ydroxylation using 2-aminophenyloxazoline as the directing group (Scheme 15b). [26] In this transformation, the use of O 2 as oxidant and water as additive is crucial for achieving high conversion.…”
Section: C à Ob Ond Formationmentioning
confidence: 99%